Improving CT-guided transthoracic biopsy diagnostic yield of lung masses using intraprocedural CT and prior PET/CT fusion imaging - Yue Lin; Yanyan Xu; Jie Lin; Liping Fu; Hongliang Sun; Zhenguo Huang; Bee Yen Ooi; Sheng Xie (BMC Pulmonary Medicine, 2022)
Abstract Objective The purpose of this study was to evaluate the usefulness of intraprocedural CT and prior PET/CT fusion imaging in improving the diagnostic yield of CT-guided transthoracic core-needle biopsy (CNB) in lung masses. Methods In total, 145 subjects with lung masses suspicious for malignancy underwent image-guided transthoracic CNB. According to imaging modality the subjects were divided into two groups. PET/CT images obtained no more than 14 days before the biopsy were integrated with intraprocedural CT images. The integrated or fused images were then used to plan the puncture sites. The clinical characteristics, diagnostic yield of CNB, diagnostic accuracy rate, procedure-related complications and procedure duration were recorded and compared between the two groups. Final clinical diagnosis was determined by surgical pathology or at least 6-months follow-up. The diagnostic accuracy of CNB was obtained by comparing with final clinical diagnosis. Results 145 subjects underwent CNB with adequate samples, including 76 in fusion imaging group and 69 in routine group. The overall diagnostic yield and diagnostic accuracy rate were 80.3% (53/66), 82.9% (63/76) for fusion imaging group, 70.7% (41/58), 75.4% (52/69) for routine group, respectively. In addition, the diagnostic yield for malignancy in fusion imaging group (98.1%, 52/53) was higher than that in routine group (81.3%, 39/48). No serious procedure-related complications occurred in both two groups. Conclusion CNB with prior PET/CT fusion imaging is particularly helpful in improving diagnostic yield and accurate rate of biopsy in lung masses, especially in heterogeneous ones, thus providing greater potential benefit for patients.